P56. The effect of aging on bilateral coordination: differences between mirror and non-mirror movements in a circle-drawing task. Issue 8 (August 2018) - Shih, P.C.; Steele, C.; Nikulin, V.; Villringer, A.; Sehm, B.
Abstract : Upper limb bilateral coordination is not only crucial for our daily living, but it is also a potential predictor for the mobility decline in the elderly. Therefore, we here investigate how aging affects bilateral coordination using a motor paradigm that includes 2 different conditions capturing fundamental aspects of bimanual control: mirror-symmetrical movement (MSM) and non-mirror-symmetrical movement (NMSM). While previously, we highlighted differential kinematic characteristics of NMSM and MSM showing that MSM are conducted with higher coupling between both limbs, we here emphasize on the effect of aging on both movement modes. Hence, we recruited twenty-five young (female: 13) and twenty-five old (female:13) healthy, right-handed volunteers, who performed a metronome-based circle drawing tasks with NMSM and MSM conditions. Compared to young participants, the elderly showed a higher auditory-motor asynchrony (young: 114.9 ± 16.85 ms, old: 218.2 ± 19.56 ms, F = 9.399, p < .005), and performed with a larger mean phase difference between hands (young: 3.6 ± 1.68°, old: 11.4 ± 1.54°; F = 22.86, p < .001) irrespective of the movement modes. Importantly, during the NMSM condition, the synchronization between hands dropped in the elderly compared to the young adult (young: 0.94 ± 0.0094, old: 0.96 ± 0.0021; F = 17.21, p < .001), an effect that was not observed in the MSM mode (young: 0.98 ± 0.0054, old: 0.98 ± 0.0055; F = .307, p = .582). In conclusion, aging has a general impact on upper limb performance during bilateral coordination. However, inter-limb coordination during MSM seems to be insusceptible to age-related motor decline. This feature of MSM might suggests differential control processes involved in these coordination patterns, an issue that might convey a new perspective on motor rehabilitation strategies after stroke that use bilateral active movements.